Análise experimental da redução de arrasto por efeito da utilização de superfícies rugosas em escoamentos turbulentos em canais retangulares - Potosi Rosero, Cristian Mauricio (2018)
Studies about fluid flow based on drag reduction are important topics in fluid mechanics. Applications in different industry sectors, such as the petroleum industry that represents one of the Brazilian economy pillars, motivate the depevelopment of experiments to find a varity of factors that modify the drag reduction. This work analyses the effect of rough elements distribution and size in the friction coefficient value in turbulent flows. To achieve this goal, four bidimensional channels with different roughness were built. The friction factor variation of a newtonian fluid for several Reynolds number values was calculated using pressure drop information. The results of these experiments were compared with data from literature. Finally, the Particle Image Velocimetry technique is used to study rough elements effects in the velocity fields and the turbulent statistics of the flow for different configurations.